A Novel Direct Liquid Injection Low Pressure Chemical Vapor Deposition System (DLI‐LPCVD) for the Deposition of Thin Films1 . Issue 8 (12th May 2017) - Vervaele, Mattias; De Roo, Bert; Debehets, Jolien; Sousa, Marilyne; Zhang, Luman; Van Bilzen, Bart; Seré, Stephanie; Guillon, Herve; Rajala, Markku; Seo, Jin Won; Locquet, Jean‐Pierre
Abstract : In this work, the use of a newly developed direct liquid injection low pressure chemical vapor deposition (DLI‐LPCVD) system is described, which allows for the deposition of thin films in a controlled and reproducible manner. The capabilities of this system are described via silica thin films deposited using the precursor tetraethyl orthosilicate (TEOS). The deposition of thin films is controlled by parameters, such as deposition temperature, partial pressure of the gases, and flow rate of the precursor solution. The thickness of the deposited layer is varied simply by changing deposition temperature and time. X‐ray reflectivity and spectroscopic ellipsometry of the deposited samples show that the thickness of the layers is well controlled by deposition temperature and time. Auger electron spectroscopy, in addition, motivates our choice to use cyclohexane as a solvent. A growth rate of 12.2 Å min −1 is obtained. Atomic force microscopy, Rutherford backscattering spectroscopy, Fourier transform infrared spectroscopy, and drop shape analysis are used to measure roughness, composition, and hydrophobicity. Thin films of silicon dioxide are successfully grown by the newly developed DLI‐LPCVD system. This system can be used for a wide range of films by varying the precursors. Abstract : This work describes the use of a newly developed direct liquid injection ‐ low pressure chemical vapor deposition (DLI‐LPCVD) system, which allows for the deposition of thin films in a controlled and reproducible manner. We describe the capabilities of this system via silica thin films deposited using the precursor tetraethyl orthosilicate (TEOS).